1999
DOI: 10.1063/1.479523
|View full text |Cite|
|
Sign up to set email alerts
|

The electronic structure of MoC and WC by anion photoelectron spectroscopy

Abstract: Articles you may be interested inStrong electron correlation in UO2 −: A photoelectron spectroscopy and relativistic quantum chemistry study Electronic structure of vanadium cluster anions as studied by photoelectron spectroscopy Photoelectron spectra of MoC Ϫ and WC Ϫ are reported at two detachment energies, 532 and 355 nm. The electron affinities of MoC and WC were measured to be 1.358 ͑0.010͒ and 1.022 ͑0.010͒ eV, respectively. Seven low-lying electronic states were observed for MoC within 2 eV above its gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Transition metal carbides have a long and rich history of experimental and theoretical studies. A possible motivation for these studies is that the transition metal catalysts find extensive use in reforming petroleum-based products. Thus, there is a compelling need to comprehend the nature of metal−carbon bonds, as this could aid in the understanding of catalytic selectivity and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal carbides have a long and rich history of experimental and theoretical studies. A possible motivation for these studies is that the transition metal catalysts find extensive use in reforming petroleum-based products. Thus, there is a compelling need to comprehend the nature of metal−carbon bonds, as this could aid in the understanding of catalytic selectivity and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest molecule formed by the interaction of Mo and C is MoC, with its ground electronic state being 3 Σ − and the electronic configuration being 1σ 2 1π 4 2σ 2 1δ 2 . 133,134 The structures of molybdenum carbide clusters of increasing sizes were investigated by Gao 135 and Cruz-Olvera. 136 138 In bulk form, molybdenum carbides are usually characterized by five different crystal phases (Figure 23): 139 α- 142 γ-MoC, 143 and η-MoC,.…”
Section: When Carbon Meets Molybdenummentioning
confidence: 99%
“…It readily forms oxides, sulfides, or carbides. The simplest molecule formed by the interaction of Mo and C is MoC, with its ground electronic state being 3 Σ – and the electronic configuration being 1σ 2 1π 4 2σ 2 1δ 2 . , The structures of molybdenum carbide clusters of increasing sizes were investigated by Gao and Cruz-Olvera . For Mo 2 C x ( x = 2–6) clusters, all of the optimized structures maintain a Mo–Mo bond, with the bond length increasing with the number of C atoms.…”
Section: When Carbon Meets Molybdenummentioning
confidence: 99%
“…43 Puretzsky and coworkers 44 detected (WC 4 ) m − , m = 1−8 clusters via laser desorption Fourier transform mass spectrometry of the photolysis of W(CO) 6 . Another experimental study on anionic clusters was provided by Li and coworkers; 45 in that study, by means of photoelectron spectroscopy of WC − , the authors reported electron affinities for WC and for six low-lying electronic states within 2.4 eV above the ground state. They also reported differences in bonding and spectroscopic properties between WC and MoC.…”
Section: ■ Introductionmentioning
confidence: 99%